Appendicular schistosomiasis: a cause of clinical acute appendicitis? - Satti, M B (1987)
The role of schistosomes in the pathologenesis of acute appendicitis in an endemic area was investigated. Of 1600 appendicectomies received in our laboratory, 26 showed appendiceal schistosomiasis, which prompted what we believe to be the first detailed histopathological evaluation of all appendices with schistosomal infestation, without prior knowledge of the clinical and operative diagnoses. The results suggest that there are two types of schistosomal appendicitis, each with distinct clinicopathological features and different pathogenetic mechanisms. They could be called obstructive and granulomatous schistosomal acute appendicitis, respectively.